How do you solve x^2-7x-6=0 using the quadratic formula?

1 Answer
Aug 10, 2015

x=(7+sqrt(73))/(2) or x=(7-sqrt(73))/(2)

Explanation:

The quadratic formula states that for a quadratic equation ax^2+bx+c, its roots, x can be computed as x = (-b+-sqrt(b^2-4ac))/(2a)

Consider the quadratic equation x^2-7x-6=0. It has coefficients a=1, b=-7 and c=-6. To solve for x, we plug these numbers into the quadratic formula.

x = (-(-7)+-sqrt((-7)^2-4(1)(-6)))/(2(1))
x = (7+-sqrt(73))/(2)

Hence, x=(7+sqrt(73))/(2) or x=(7-sqrt(73))/(2)